Digital Divide Challenges and Their Impact on Teaching and Learning in Secondary Schools in Anambra State - Ijeoma Okenwa-Fadele; Ahmed Ademola Oyeyemi; Emillia Chinenye Akutaekwe; Goodseed Chidera Felix; Balami Daniel Ibrahim (Journal of Research in Education and Pedagogy, 2025)
The world is becoming a global village where conventional teaching and learning is changing to meet the 21st century innovation demands in terms of technological advancement in service delivery in education all over the world. This research explores the challenges associated with the digital divide and its effects on instructional practices in public secondary schools within Awka South Local Government Area, Anambra State. The study was structured around three guiding questions and a single hypothesis assessed at a 0.05 level of significance. Utilizing a descriptive survey design, the study sampled 122 teachers from a population of 488 across 19 secondary schools, selected through simple random sampling. Data collection employed a validated 15-item instrument, demonstrating a reliability index of 0.74 using Cronbach’s alpha. Results indicated a significant relationship between digital divide components, specifically accessibility, and their educational consequences and effective teaching and learning. Key statistical results include: r = 0.607 and r = 0.542 (p < 0.05). Additionally, the regression model (F (4,118) = 20.271; p < 0.05) highlighted that digital divide variables collectively accounted for notable variations in instructional outcomes. Both access challenges (β = 0.449) and impact-related issues (β = 0.251) significantly influenced outcomes. Based on these insights, the study recommends, among other that the government should provide secondary schools with adequate facilities and equipment necessary to ensure that the digital divide is relinquished. This will go a long way to see that no school is left behind in the utilization of digital tools. Additionally, suggestions for further studies were made.